A de Novo EDA-Variant in a Litter of Shorthaired Standard Dachshunds with X-Linked Hypohidrotic Ectodermal Dysplasia. Issue 1 (1st January 2019) - Vasiliadis, Danae; Hewicker-Trautwein, Marion; Klotz, Daniela; Fehr, Michael; Ruseva, Stefka; Arndt, Jennifer; Metzger, Julia; Distl, Ottmar
Abstract: In this study, we present a detailed phenotype description and genetic elucidation of the first case of X-linked hypohidrotic ectodermal dysplasia in the shorthaired standard Dachshund. This condition is characterized by partial congenital hypotrichosis, missing and malformed teeth and a lack of eccrine sweat glands. Clinical signs including dental radiographs and histopathological findings were consistent with ectodermal dysplasia. Pedigree analysis supported an X-recessive mode of inheritance. Whole-genome sequencing of one affected puppy and his dam identified a 1-basepair deletion within the ectodysplasin-A (EDA) gene (CM000039.3:g.54509504delT, c.458delT). Sanger sequencing of further family members confirmed the EDA: c.458delT-variant. Validation in all available family members, 37 unrelated shorthaired standard Dachshunds, 128 further Dachshunds from all other coat and size varieties and samples from 34 dog breeds revealed the EDA: c.458delT-variant to be private for this family. Two heterozygous females showed very mild congenital hypotrichosis but normal dentition. Since the dam is demonstrably the only heterozygous animal in the ancestry of the affected animals, we assume that the EDA: c.458delT-variant arose in the germline of the granddam or in an early embryonic stage of the dam. In conclusion, we detected a very recent de-novo EDA mutation causing X-linked hypohidrotic ectodermal dysplasia in the shorthaired standard Dachshund.